MACKINDER’S “HEARTLAND” THEORY AND THE ATLANTIC COMMUNITY - SHARAPOVA, Sevara (CENTRAL ASIA AND THE CAUCASUS, 2005)
The term “Atlantic partnership” refers to the strong diplomatic and military links between the U.S. and major Western European countries such as Great Britain, Germany and France. The union established by these countries has been durable and reliable, especially during the Cold War. The European allies consistently supported the U.S. in military actions. However, in spite of dependence on the U.S., even during the Cold War the European states had many trade conflicts with the United States.Nowadays both security and economic issues have emerged as weak points in the Atlantic relationship. The President of the U.S., G.W. Bush, paid his first visit after reelection for the second term in February 2005 to European countries with the aim of improving these relations. The Atlan-tic relationship was put under strain when some European partners of the U.S. rejected participation in the U.S.-led military action against Iraq in 2003. This article will address the questions of why some European countries refused to support that military action, and how they responded to it.France and Germany were the most prominent states that refused to side with the U.S. over Iraq. Historically, France’s foreign policy has been characterized by the “traditional De Gaulle style "which, with some qualification, represents two important trends. On the one hand, it stresses friendship with Washington and NATO (the North Atlantic Treaty Organization) to provide an opportunity of balance in transatlantic relations. On the other hand, it seeks the renewal of European military forces to provide some distance from Wash-ington.1 As for Germany, it has always sided with U.S. military actions since World War II. In 2003 Germany broke with that policy for the first time.